2021
DOI: 10.1016/j.ctro.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine therapy with accelerated Partial breast irradiatiOn or exclusive ultra-accelerated Partial breast irradiation for women aged ≥ 60 years with Early-stage breast cancer (EPOPE): The rationale for a GEC-ESTRO randomized phase III-controlled trial

Abstract: Breast cancer in the elderly has become a public health concern; there is a need to re-design its treatment with a view to de-escalation. Our paper sets out the rationale for a phase 3 randomized trial to evaluate less burdensome adjuvant procedures that remain effective and efficient. Materials and methods: For low-risk breast cancer in the elderly, adjuvant treatment has been adjusted in order to make it more suitable and efficient. Hypofractionated radiation therapy based on accelerated or non-accelerated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…Furthermore, ET is associated with limiting toxicity and a reduced quality of life in patients included in these randomized de-escalation trials [ 20 ]. Therefore, randomized trials are already ongoing not only to address the role of hormonal therapy vs. APBI regarding cancer control but also the quality of life [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ET is associated with limiting toxicity and a reduced quality of life in patients included in these randomized de-escalation trials [ 20 ]. Therefore, randomized trials are already ongoing not only to address the role of hormonal therapy vs. APBI regarding cancer control but also the quality of life [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equivalence of accelerated partial breast radiation delivered by external beam has been demonstrated in several clinical trials and endorsed for women with tumors with favorable biology, and together with ultra-hypofractionation, may be an attractive option in resource-restricted regions. Investigations for further de-intensifying radiation schedules using ultra-accelerated partial breast radiation as a single fraction are being planned to be tested against accelerated partial breast radiation + endocrine therapy [199,200].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to deintensification, the EUROPA trial is comparing RT alone to endocrine therapy alone 49. Likewise, the GEC-ESTRO Breast Cancer Working Group has conceived a phase III randomized trial using multicatheter interstitial brachytherapy, EPOPE, which is designed to test 30 to 32 Gy in 7 to 8 fractions versus 16 Gy in a single fraction, with the primary endpoint of disease-free survival 50. In addition, trials are evaluating shorter courses of PBI.…”
Section: Discussionmentioning
confidence: 99%
“…49 Likewise, the GEC-ESTRO Breast Cancer Working Group has conceived a phase III randomized trial using multicatheter interstitial brachytherapy, EPOPE, which is designed to test 30 to 32 Gy in 7 to 8 fractions versus 16 Gy in a single fraction, with the primary endpoint of disease-free survival. 50 In addition, trials are evaluating shorter courses of PBI. For example, initial outcomes from the TRI-UMPH-T trial demonstrated the safety and feasibility of a 3 fraction PBI approach with further outcomes expected in the years to come; in addition, advances in treatment technology have allowed for the evaluation of a single-fraction postoperative PBI approach.…”
Section: Future Directionsmentioning
confidence: 99%